Depression in Ugandan caregivers of cancer patients: The role of coping strategies and social support - Nuwamanya, Simpson; Nkola, Rahel; Najjuka, Sarah Maria; Nabulo, Harriet; Al‐Mamun, Firoj; Mamun, Mohammed A.; Kaggwa, Mark Mohan (Psycho‐Oncology, 2023)
Background: Palliative care services involve the psychological care of the caregivers of cancer patients. Psychological conditions, especially depression among caregivers, distort caregiving roles; thus, it can increase a patient's psychological suffering. Objective: To determine the prevalence of depression and associated coping strategies among caregivers of cancer patients at a rural cancer care facility. Methods: This cross‐sectional study was among 366 caregivers of cancer patients. The data was collected using a pretested questionnaire, where the symptoms of depression were assessed using the Patient Health Questionnaire‐9 at a cutoff of 10 out of 27. The coping strategies were assessed based on the Brief‐coping orientation to problems experienced Inventory. Logistic regression was used to determine the factors associated with depression. Results: The mean age of the participants was 39.01 (11.50) years; most were females (60.38%). The prevalence of depression was 8.2%. The identified factors associated with increased likelihood of depression were coping strategies: active coping (aOR = 1.55, 95% Confidence Interval (CI) = 1.05–2.28, p = 0.026), denial (aOR = 1.62, 95% CI = 1.20–2.19, p = 0.001), and humor (aOR = 1.43, 95% CI = 1.11–1.84, p = 0.005). However, coping with positive reframing reduced the likelihood of depression (aOR = 0.70, 95% CI = 0.52–0.94, p = 0.019). There was no significant association between depression and social support. Conclusion: The lower prevalence of depression reported in this study than in the prior Ugandan studies reflects that depression severity among caregivers in rural settings is less prevalent because of the fewer care‐associated burdens they experience. Therefore, establishing palliative care near the patients can be a protective factor for caregivers' depression. In addition, the role of social support and coping strategies in depression might be helpful in mental health strategies
Keywords: Active coping; Cancer; Caregivers; Coping strategies; Denial; Depression; Humor; Oncology; Palliative care; Psycho‐oncology; Rural cancer facility